Aortic Arch Aneurysm Repair under Deep Hypothermic Circulatory Arrest - Pokharel, Jeju Nath; Upreti, MR; Shakya, DR; Koirala, Bhagwan; Sharma, Jyotindra; Pradhan, S; Timila, R; Rajbanshi, B; Choudhary, SN; Bhatta, M; Khan, U (Nepalese Heart Journal, 2017)
A 46 years female underwent aortic arch repair surgery under deep hypothermic circulatory arrest (DHCA) and right antegrade cerebral perfusion. The patient was extubnated after 13 hours of the surgery and discharged from SICU on third post operative day and discharged from hospital on sixth postoperative day uneventfully and with excellent neurological functions. It was the first case of aortic arch repair in our hospital. Combination of DHCA and right antegrade cerebral perfusion may be the reason for better neurological outcome.